Analisis Islamic Corporate Governance Dalam Meningkatkan Kualitas Kinerja Karyawan Perbankan Syariah - Haya, Anindhita Fadia; Indrawati, Santi; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The rapid development of Islamic Banks has led to various efforts to overcome this competition. One of them is to improve the quality of employee performance by implementing Islamic Corporate Governance (ICG). This study aims to look at the existing implementation of ICG and the performance of employees that can affect the existing fundraising. The research method used is the study of literature. The results of this study indicate that Islamic Corporate Governance can improve the quality of employee performance which is marked by good employee work results such as service and productivity so that it can attract people to provide sponsorship. However, if one of the principles is not optimal, the employee's performance will still increase but not optimal.